Analisis Faktor-Faktor yang Mempengaruhi Penentu Belanja Online: Studi pada Perilaku Konsumen Belanja Online Produk Pakaian Jadi Melalui Situs Online Zalora atau Lazada di Daerah Istimewa Yogyakarta - Christian Aditya; Titik Kusmantini; Yuli Liestyana (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2020)
Online shopping is an activity of buying and selling by utilizing the development of internet technology. The higher level of online shopping consumers has led to the phenomenon of e-commerce, like Zalora and Lazada. Consumers of online shopping in Special Region of Yogyakarta conducting online shopping activities are influenced by factors such as perception of easy to use, perception of perceived benefits, perception of risk, trust, consumer attitudes and online shopping interests. The design of research is descriptive and quantitative research using incidental sampling method. Data collection technique is carried out by distributing questionnaires using Google forms with the number of samples studied is 155 respondents. In order to test the hypothesis, Structural Equation Modeling (SEM) is used with analysis technique based on Partial Least Square (PLS). The results of this study show that 1) There is a positive and significant effect of perception of easy to use on consumer attitudes, 2) There is a positive and significant effect of perception of perceived benefits on consumer attitudes, 3) There is a negative and insignificant effect of risk perception on consumer attitudes, 4) There is a positive and significant influence of trust on consumer attitudes, 5) There is a positive and significant influence of consumer attitudes on online shopping interest.